Race, class and Christianity in South Africa : middle-class moralities - Abraham, Ibrahim (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book is an exploration of the relationship between race and class in the specific context of middle-class Christianity in South Africa. The author offers a theoretically sophisticated and empirically rich study of middle-class Christians in contemporary South Africa, as they seek to live good lives and build a good society. Focused on the city of Cape Town, drawing upon ethnographic research in conservative and progressive multiracial Protestant churches, furnished with critical analysis of South African literature and popular culture, this timely study explores expressions of ambition and anxiety that are both spiritual and material. Building upon debates over middle class identity and morality from sociology, anthropology and cultural studies, this book analyses congregational attempts at social unity through worship music and creative youth ministry, discussions on white privilege and shame, and the impact of middle-class black activism in South African churches and society. This book will of interest to scholars of South African culture and society, religion, anthropology and sociology"--
Introduction: Day Zero in Cape Town -- Christianity and the middle class in South Africa -- Middle-class morality and Christianity in South Africa -- Spiritual and class insecurity in South Africa -- Middle-class moral insecurity in South Africa -- Race, class, and habitus in South African churches -- Anomie and vocation in South African Christian ministry -- Musicking, unity, and sincerity in South African churches -- Conclusion: Covid-19 in Cape Town.
Keywords: Middle class -- Religious life -- South Africa; Christianity -- South Africa; Race relations -- Religious aspects -- Christianity; South Africa -- Race relations; SOCIAL SCIENCE / Social Classes